Differential biochemical and metabolic responses of contrast rice cultivars ( Oryza sativa L.) under salt stress - Cuong Quoc Duong; Anh Lan Bui; Thia Hong Le; Truc Thanh Tran; Nam Ngoc Trinh (Acta Agrobotanica, 2023)
More than half of the global population uses rice as the fundamental staple food; therefore, it is one of the most popular crops in the world. However, it is susceptible to salt stress, particularly among monocot crops, which reduces rice cultivation yield and threatens global food security. This research investigates the role of some factors, including amino acids, antioxidant enzymes, and sugars, in the response to the salinity stress of three contrasting rice cultivars, Dai Thom 8 (salt-sensitive), OC 10 (moderately salt-tolerant), and OM 9577 (salt-tolerant) in the seedling stage. The salt-tolerant varieties exhibited remarkable differences in physiological and biochemical traits, including enhancement of growth capacity, reduction of cell membrane damage via lowering lipid peroxidation, minimization of ROS generation, enhancement of free radical scavenging activity, and SOD, POD, and CAT enzyme activities. Additionally, the study analyzed the presence of 13 sugars using GC-MS and found that all three rice cultivars shared seven common sugars in similar quantities. However, OM 9577 had a higher content of the other six sugars compared to OC 10 and Dai Thom 8. It is one of the important biochemical factors responsible for the difference in the response mechanism to NaCl stress among rice varieties, specifically lyxofuranose (3.268%), a-D-xylopyranose (5.727%), mannopyranose (12.86%), α-D-glucopyranose (6.399%), ß-D-glucopyranose (5.509%), and D-arabinose (1.512%). Furthermore, the quantification of 20 amino acids through HPLC-DAD revealed that the salt-tolerant rice cultivars had higher concentrations of 11 amino acids than the salt-sensitive ones, including proline, isoleucine, serine, ornithine, histidine, glutamic acid, asparagine, alpha-alanine, aspartic acid, glutamine, and valine. These findings provide promising biochemical indicators for selecting salt-tolerant rice cultivars or improving existing varieties through traditional hybridization or gene transfer methods. Understanding these responses can significantly contribute to enhancing rice cultivation and ensuring food security in regions facing salinity challenges.